Spectroscopic Definition of the CuZ° Intermediate in Turnover of Nitrous Oxide Reductase and Molecular Insight into the Catalytic Mechanism - Johnston, Esther M. (2022)
Fundacao para a Ciencia e Tecnologia - PTDC/QUI-BIQ/116481/2010, PTDC/BBB-BQB/0129/2014, SFRH/BD/87898/2012 ; Unidade de Ciencias Biomoleculares Aplicadas-UCIBIO - FCT/MEC - UID/Multi/04378/2013 ; ERDF - POCI-01-0145-FEDER-007728